2020
DOI: 10.12968/ortu.2020.13.2.50
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic pain

Abstract: Pain is a common side-effect of orthodontic treatment. The aetiology of orthodontic pain, pain pathways and pain management will be described. CPD/Clinical Relevance: An understanding of the cause and subsequent management of orthodontic pain is essential for any orthodontist in order to improve patient co-operation and satisfaction with treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Six hours after the placement of the fixed orthodontic appliance, the pain had a decreasing trend. Similarly, Grewal et al [ 15 ], Shenoy et al [ 16 ], Eslamian et al [ 17 ], and Topolski et al [ 18 ] reported that the peak of pain was experienced six hours after the beginning of the orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Six hours after the placement of the fixed orthodontic appliance, the pain had a decreasing trend. Similarly, Grewal et al [ 15 ], Shenoy et al [ 16 ], Eslamian et al [ 17 ], and Topolski et al [ 18 ] reported that the peak of pain was experienced six hours after the beginning of the orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be a sign of other problems that need attention. Managing pain promptly helps patients feel comfortable, improves treatment results, and ensures satisfaction with orthodontic care [ 4 , 18 ]. With the internet’s widespread distribution, people are increasingly turning to online sources for educating themselves with information about their health concerns and treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to improve how to manage pain and discomfort, orthodontists must gain an understanding into the pain produced by orthodontic procedures. Orthodontists can better help patients by improving pain management and enhancing acceptance of required treatment stages with a more educated viewpoint [ 18 ]. This results in greater adherence to the intended procedure and more satisfaction with overall outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…14 Pain is a highly subjective experience. 28 The perception of pain covers various multidimensional aspects, and its intensity and discomfort can be expressed in different ways. 29 Earlier studies evaluated patients' perceptions only up to 6 months after debonding.…”
Section: Main Findings In the Context Of The Existing Researchesmentioning
confidence: 99%